Blending Personal Health, Family Matters and Personal Time Management for the Best Work-life Balance - Saad, Mazni; Jaafar, Aishah Nawwarah; Ong, Mohd Hanafi Azman; Yulinda, Eni; Kumarasamy, Mokana Muthu; Mahmod, Razmah (Advances in Social Sciences Research Journal, 2024)
This paper aims to develop a theoretical perspective to better understand hospitality workers’ behaviours in blending family life and work for the best work-life balance. The perspective is guided by social exchange theory. It examines hospitality workers’ behaviour that has high levels of positive valence to be most influential for their work-life balance due to profitable relationships. We describe these theoretical principles and sub-principles concerning hospitality workers to build a research agenda to encourage future research. A response rate of 28% from food and beverage companies participated in the online survey via the web-based questionnaire design. The results indicate that family matters, time management, and personal health bring 60% of predictions for F&B workers’ work-life balance. Three predictors were positive and significantly affected the work-life balance, with personal health being the biggest influence, followed by family matters, and time management. Implications, limitations, and recommendations are also discussed at the end of this paper.